Have a guide on appointing retired clinicians as teaching staff - Ismail, Ahmad Faisal (New Straits Times Press (M) Bhd., 2020)
THE academic titles, namely associate professor and professor, are academic ranks that identify one’s scholarly position in academia. The word “professor” derives from Latin, which literally translates as “one who professes”.